SISTEM TERPUSAT PENGATURAN RELAY SEBAGAI SAKLAR LISTRIK PADA GEDUNG MULTI RUANG MENGGUNAKAN PC - , RANDI WIYARAGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The function of most major computer network is for data communication. This function can be expanded to control electrical equipment that is located quite a distance, for example in areas of large and spacious building or house that is located away from the office. By utilizing the UDP protocol and the Delphi programming language, some electrical equipment can be controlled through a computer network. Moreover, computers now become cheaper and cheaper. Using a cheap computer to control electrical appliances becomes more profitable.